Towards evidence-based classification in para-cycling - Liljedahl, J. (Avhandlingsserie för Gymnastik- och idrottshögskolan, 24, 2022)
The aim of classification in Paralympic sport is to minimize the impact of impairment on the outcome of competition. The aim of this thesis was to investigate the impact of different types of impairments on para-cycling performance to develop an evidence-based classification system in the para-cycling C (bicycling) and T (tricycling) divisions.